Effect of Aromatherapy with Orange Essential Oil on Nausea and Vomiting in Children after Tonsillectomy Surgery - Narges Sadeghi; Fatemeh Pak Nodehi; Mina Mohammadi (Hamadan University of Medical Sciences, 2022)
Background and Objective: Adenotonsillectomy is one of the most common surgeries performed on children today and is often the first operation a child undergoes. Postoperative nausea and vomiting are among the common and annoying complications after anesthesia and surgery. This study was conducted to determine the effect of aromatherapy with orange essential oil on nausea and vomiting in children after tonsillectomy. Materials and Methods: This study randomized clinical trial was conducted on 64 children in Amir al-Momenin Hospital in Rasht, Iran, who were selected by the available sampling method. Data were collected using a demographic information questionnaire, a questionnaire assessing the severity of nausea and vomiting during 6 hours of the intervention based on a visual analog scale, and the amount of nausea and vomiting in children 12 hours after the intervention using the Adapted Rhodes Index of Nausea and Vomiting for Pediatrics by Child questionnaire. Data were analyzed in SPSS software (version 22) using descriptive statistics and independent t-test or analysis of variance with repeated observations. Results: The mean intensity of nausea and vomiting during 6 hours of intervention was significantly different in the two groups (P<0.001). The mean intensity was obtained at 11.23±2.25 in the aromatherapy group and 15.31±1.43 in the placebo group. Statistically, which was significantly different (P>0.001). There was a significant difference in the mean of nausea and vomiting of children in the placebo and aroma treatment groups within 12 hours after the intervention (P<0.001). Conclusion: Based on the results of the present study, aromatherapy with orange essential oil had an effect on the severity of nausea and vomiting in children after tonsillectomy. Therefore, this issue must be taken into the consideration in educational programs by the officials of nursing education and medical centers.